1999
DOI: 10.1143/jjap.38.5762
|View full text |Cite
|
Sign up to set email alerts
|

Role of Seed Crystal Layer in Two-Step-Growth Procedure for Low Temperature Growth of Polycrystalline Silicon Thin Film from SiF4 by a Remote-Type Microwave Plasma Enhanced Chemical Vapor Deposition

Abstract: Role of seed crystal layer which played in low temperature growth of polycrystalline silicon (poly-Si) thin films was investigated by two-step-growth (TSG) process. The TSG involves two different deposition processes, which are called as `seed process' and `growth process'. In order to satisfy the conflicting demands such as low temperature, high rate and high quality crystal growth, the deposition conditions in the seed and growth processes were examined. As a result, it is confirmed that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…7,8) It has been well known that increasing the H 2 dilution ratio not only facilitates transition from the incubation-layer growth to the microcrystallinefilm growth, 4,5) but also helps increase the crystalline volume fraction (called crystallinity in this paper) of the film. 2) Our previous study showed that a dilution ratio as high as SiH 4 /H 2 ∼ 0.003 is also effective to reduce the thickness of the incubation layer to a large extent.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…7,8) It has been well known that increasing the H 2 dilution ratio not only facilitates transition from the incubation-layer growth to the microcrystallinefilm growth, 4,5) but also helps increase the crystalline volume fraction (called crystallinity in this paper) of the film. 2) Our previous study showed that a dilution ratio as high as SiH 4 /H 2 ∼ 0.003 is also effective to reduce the thickness of the incubation layer to a large extent.…”
Section: Introductionmentioning
confidence: 91%
“…4) The initial layer near the substrate, however, remains amorphous and is called an incubation layer. There have been many studies on the mechanisms of nucleation of the microcrystalline Si after the incubation layer is formed, 5) as well as on grain growth of the nucleated microcrystals. 6) On the other hand, little is understood regarding the formation mechanism of the incubation layer itself, although this layer is undesirable for most device applications.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, many attempts have been made to improve crystallinity during the early stage of growth using fluorinated plasmas, e.g. SiF 4 -H 2 plasmas [86,87] and CF 4 -He plasmas [88]. Film structure, including grain size and orientation, and crystalline fraction, can be controlled even at the early stage of growth by pre-treatments and modification of the substrate surface.…”
Section: The Substrate-film Interface: the Sif 4 Substrate Pre-treatmmentioning
confidence: 99%
“…3 Results and discussions 3.1 High-quality initial seed layer In order to decrease the a-Si:H incubation layer thickness in the initial growth of µc-Si:H i-layer, a two-step growth method has been widely employed, where an initial seed layer was formed firstly, and subsequently, the rest part of film [10,11]. The general way to deposit the initial seed layer is just to decrease silane concentration while retaining other parameters.…”
mentioning
confidence: 99%